High-efficiency 90Sr radio-photovoltaic cells based on waveguide light concentration structure - Tongxin Jiang; Sijie Li; Wenlong Yao; Lu Han; Lei Zhang; Xue Li; Lifeng Zhang; Xian Tang; Xin Li; Haisheng San (Light: Science & Applications)
Abstract Radio-photovoltaic cells (RPVCs) are able to offer high reliability and extended operational lifetimes, making them ideal for harsh-environment applications. However, the two-stage energy conversion process inherently limits energy conversion efficiency (ECE). This study presents a novel RPVC design based on a waveguide light concentration (WLC) scheme, employing multilayer-stacked GAGG:Ce scintillation waveguides alternately loaded with 90Sr radioisotope sources. Electron beam irradiation tests revealed highly efficient radioluminescence (RL) emission from the edge surfaces of GAGG:Ce waveguide at electron energies exceeding 60 keV. A RPVC prototype incorporating 1.43 Ci of ⁹⁰Sr achieved a maximum output power (P max) of 48.9 μW, with an unprecedented ECE of 2.96%—the highest reported value for radioisotope-powered RPVCs to date. Furthermore, a multi-module integrated RPVC prototype demonstrated a P max of 3.17 mW, with a short circuit current of 2.23 mA and an open circuit voltage of 2.14 V. Remarkably, the device exhibited only 13.8% RL performance degradation after a 50-year equivalent electron beam irradiation (total fluence: 5.625 × 1018 e/cm2), confirming exceptional radiation hardness. These findings demonstrate that the WLC-based RPVCs achieve both high power output and exceptional long-term stability, representing a substantial advancement for facilitating nuclear battery applications.